РОЛЬ ЛЕКАРСТВЕННЫХ РАСТЕНИЙ В ЖИЗНИ И ЗДОРОВЬЕ ЧЕЛОВЕКА (Experimental biology, 2009)
In the review results of literary datas and own researches of antioxidant properties of medicinal herbs are presented. In article have been considered the nature, a role and mechanisms of action of the polyphenolic substances widely presented in flora and possessing a greater spectrum of antioxidant activity.
Keywords: antioxidant properties; olyphenolic substances